Aircraft selection - with particular reference to the Aer Lingus selection of the BAC one - eleven - Dempsey, J. F. (Statistical and Social Inquiry Society of Ireland, 1965)
Conditions in the technical development of the aeroplane at the present time, especially the absence of any important improvements in design or in motive power and the uncertainty about the prospects for supersonic transport, as well as general economic considerations, tend to lengthen its useful life period. Development costs also are now weighing more heavily on manufacturers of commercial aircraft and in turn on airline operators. The airlines consequently have begun to realise that the rate of replacement heretofore accepted has been imposing too great a strain on their resources. There are several considerations that could shorten or extend the life of an aeroplane as a transport vehicle in the front rank. They relate particularly to its competitive qualities, its reliability, size, speed and operating unit costs.
Read before the Society, 2 April 1965
Keywords: State enterprises; Aircraft selection; Aer Lingus; Public procurement; 314.15